Efektivitas Penerapan Model Discovery Learning dengan Pendekatan ICARE dalam Pembelajaran Matematika - Darwis, Muhammad; Asdar; Kurniati (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
The purposes of the research were to investigate the effectiveness of the application of discovery learning model with ICARE approach in mathematics learning of grade VII SMP Negeri di Sungguminasa. The effectiveness of learning can be measured based on the results of students’ learning achievement, students’ activity, and students’ responses after the implementation of learning. The design of the research, was Pre-Experiment. The population in this research are all of grade VII students of SMP Negeri 1 Sungguminasa. The samples of this research are one class. The sampling of this research is cluster random sampling. The method of collect the data used questionnaire, observation and test. The technique of data analysis used is the technique descriptive and inferential statistical analysis. The results analysis of this research are: 1) The scores of students’ learning achievement there was a significant increase and passing the Minimum Completeness Criteria on score 70 with the mean score of students’ learning achievement is 74,16. (2) Students’ classical completeness is 87,5%. (3) The implementation of learning are in the category carried out very well. (4) The students’ activities are on very good category (5) The students’ responses are tend to be positive category.